Adherent-invasive E. coli – induced specific IgA limits pathobiont localization to the epithelial niche in the gut - Tanaka, Rika; Imai, Jin; Tsugawa, Hitoshi; Eap, Karl Bil; Yazawa, Masaki; Kaneko, Motoki; Ohno, Masashi; Sugihara, Kohei; Kitamoto, Sho; Nagao-Kitamoto, Hiroko; Barnich, Nicolas; Matsushima, Masashi; et al. (Frontiers in Microbiology, 2023)
Background and aim: Adherent-invasive E. coli (AIEC) has been identified as a pathobiont associated with Crohn’s disease (CD), that prefers to grow in inflammatory conditions. Although the colonization by AIEC is implicated in the progression of the disease and exacerbates inflammation in murine colitis models, the recognition and response of host immunity to AIEC remains elusive. Methods: Antibiotic treated female C57BL/6 mice were inoculated by commensal E. coli and LF82 AIEC strains. Luminal-IgA fractions were prepared from feces and their binding to AIEC and other strains was assessed to confirm specificity. IgA binding to isogenic mutant strains was performed to identify the functional molecules that are recognized by AIEC specific IgA. The effect of IgA on epithelial invasion of LF82 strain was confirmed using in vitro invasion assay and in vivo colonization of the colonic epithelium. Results: Persistent colonization by AIEC LF82 induced secretion of luminal IgA, while commensal E. coli strain did not. Induced anti-LF82 IgA showed specific binding to other AIEC strains but not to the commensal, non-AIEC E. coli strains. Induced IgA showed decreased binding to LF82 strains with mutated adhesin and outer membrane proteins which are involved in AIEC – epithelial cell interaction. Consistently, LF82-specific IgA limited the adhesion and invasion of LF82 in cultured epithelial cells, which seems to be required for the elimination in the colonic epithelium in mice. Conclusion: These results demonstrate that host immunity selectively recognizes pathobiont E. coli, such as AIEC, and develop specific IgA. The induced IgA specific to pathobiont E. coli, in turn, contributes to preventing the pathobionts from accessing the epithelium.